Lämpliga växter för växtväggar i Göteborg - Gustafsson, Malin (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2019)
Vertical gardens have become a popular subject on the construction market, therefore there has been an increased demand for knowledge in the choice of plants to be used. The purpose of this work is to find out if it is possible to increase the number of vertical gardens in Gothenburg, while taking into consideration the city’s climate. The choice of plant material has been investigated and evaluates the best plants to use for this climate. The definition of vertical gardens in this work is plants which are mounted on a vertical surface without anchoring into soil.